Integrasi Nilai Estetika Arsitektur Vernakular Taman Mayura dalam Pengembangan Model Pembelajaran Seni Rupa Berbasis Budaya Lokal di Sekolah Dasar - Gozin Najah Rusyada (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop and test the effectiveness of a visual arts learning model based on the aesthetic values of Taman Mayura’s vernacular architecture in enhancing elementary school students’ ability to appreciate and create visual art. The study employed the Research and Development (R&D) approach using the ADDIE model with an explanatory mixed-methods design, involving 30 fifth-grade students at SDN 2 Jenggala, North Lombok Regency. Data were collected through observation, semi-structured interviews, aesthetic ability tests, documentation, and expert validation. The developed products include a local culture-based teaching module, visual media on Taman Mayura’s architecture, worksheets, an art work assessment rubric, and a learning implementation guide. Validation results showed that the media achieved a feasibility score of 92% and the instructional design 89%, both categorized as highly feasible. Quantitative results showed an increase in students’ aesthetic abilities from a pre-test average of 65.3 to 83.5 on the post-test, with a paired sample t-test yielding p < 0.05. Qualitative findings indicated that students were more active in observing visual elements, composing arrangements, determining focal points, and explaining the aesthetic rationale behind the works. This study demonstrates that the integration of local culture into visual arts education can create contextual, meaningful, and responsive learning experiences that align with students’ cultural identities.